1982
DOI: 10.1021/jm00345a009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and enzymic activity of 6-carbethoxy- and 6-ethoxy-3,7-disubstituted pyrazolo[1,5-a]pyrimidines and related derivatives as adenosine cyclic 3',5'-phosphate phosphodiesterase inhibitors

Abstract: A number of 3,7-disubstituted 6-carbethoxypyrazolo [1,5-a] pyrimidines and 3,7-disubstituted 6-ethoxypyrazolo-[1,5-a]pyrimidines have been prepared and evaluated as adenosine cyclic 3',5'-phosphate (cAMP) phosphodiesterase (PDE) inhibitors vs. the low Km enzyme isolated from beef heart, rabbit lung, and kidney preparations. The results were found to be between 0.5 to 13 times as potent as theophylline as inhibitors of PDE, depending on the tissue source. A number of these PDE inhibitors exhibited significant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Using formamidine acetate and 2-methoxyethanol as a solvent, we obtained 8 in 85 % yields and >98 % HPLC purity. For the chlorination step we found that the use of thionyl chloride and DMF [6] gave less reliable results than our method using phosphoryl chloride and N,N-diethylaniline [7] where we obtained 70-86 %. The preparation of 9 is not mentioned in the literature.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Using formamidine acetate and 2-methoxyethanol as a solvent, we obtained 8 in 85 % yields and >98 % HPLC purity. For the chlorination step we found that the use of thionyl chloride and DMF [6] gave less reliable results than our method using phosphoryl chloride and N,N-diethylaniline [7] where we obtained 70-86 %. The preparation of 9 is not mentioned in the literature.…”
Section: Resultsmentioning
confidence: 71%
“…Attempts to prepare the desired chloro compound using thionyl chloride and DMF [9] gave only unsatisfactory yields. Similar to the syntheses described above, phosphoryl chloride and N, N-diethylaniline [7] proved to be advantageous. Each of the following steps could be improved substantially and the overall yield from 16 to 3 was 33 % as compared to 20 % previously [9].…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Unsubstituted or 4-alkylsubstituted 3-aminopyrazoles reacted with DEEM in acetic acid [142][143][144] giving 7-oxopyrazolo[1,5-a]pyrimidine-6-carboxylates (28) (Fig. 27), the adenosine cyclic 3',5'-phosphate phosphodiesterase inhibitors [142]. 3-aminopyrazole-4-ones under same conditions gave 4,7-dioxopyrazolo[1,5-a]pyrimidine-6-carboxylates (29) (Fig.…”
Section: Bicyclic Systemsmentioning
confidence: 99%
“…Pyrans were readily obtained in good yields on treatment of ylidene derivatives of α-cyanochalcones with active methylene nitriles and active methylene ketones. Thus, benzylidene derivatives, aminomethylene and mercaptomethylene derivatives has been reported [170,235,236] to react with active methylene reagents to yield pyran derivatives [266][267][268][269][270][271][272].…”
Section: Synthesis Of Pyran Coumarin and Condensed Pyran Derivativesmentioning
confidence: 99%